Infertility and Social Issue Have the Most Significant Impact on Health-Related Quality of Life Among Polycystic Ovarian Syndrome Women in South India - L. Hariprasath; D. Selvakumar; V. Dharani; K. K. Durgalakshmi; V. G. Abilash; T. S. Gopenath; S. Nishu (Journal of Human Reproductive Sciences)
Background: Infertility can have a significant impact on the identity of women. Individual women, who are infertile, experience tragic emotions, as well as those who are sad for great losses, like the death of a loved one. In this case, the woman is experiencing the loss of the ability to procreate. Aim: In the present study, our major concern was to implement the health-related quality of life (HRQOL) Questionnaire on South Indian polycystic ovarian syndrome (PCOS) women to assess the impact of various clinical features of polycystic ovary syndrome on the HRQOL of South Indian women diagnosed. Settings and Design: A total of 126 females in the first phase and 356 females in the second phase between the age group of 18–40 years characterised under the Rotterdam criteria were selected for the study. Materials and Methods: The study was carried out in three different phases which included a one-to-one interview, group discussion and questionnaire session. In our study, we found that all the females who attend the study showed positivity for all the domains developed in the previous study and suggested that further domain can be developed. Statistical Analysis Used: Suitable statistical methods were used with Graph pad PRISM (version 6). Results: Hence, in our study, we developed a further new sixth domain called as 'social impact domain'. Among South Indian PCOS women, we found that infertility and social issue have the most significant impact on HRQOL. Conclusion: The revised questionnaire by including the sixth domain called 'Social issue' is likely to be useful in measuring the quality of health of female having PCOS in regard to South Indian population.